Biostimulant activity of plant protein hydrolysate on the growth of Beta Vulgaris Subs. Vulgaris (linn.) - GAYATHRI SUKUMAR; DIVYALAKSHMI D; MITHULA S; S.RUPACHANDRA; ANINDHITA MEENA M; P.MUTHULAKSHMI (International Journal of Pharma and Bio Sciences, 2017)
Natural biostimulants hold a huge promise for the future of agriculture. They assist the plant growth throughout the crop’s life from seed germination to plant maturity. In this regard, natural biostimulants like protein hydrolysates are gaining more attention, since they can act as an alternative source for chemical fertilizers. Protein hydrolysates display hormone like function and influence plant metabolism by interacting with biochemical processes and physiological mechanisms, such as glycolysis and nitrogen assimilation. Wheat gluten hydrolysate a natural protein biostimulant has been known to have oligopeptides, polypeptides and free amino acid which can exhibit a hormone like activity resulting in an increased nitrogen uptake hence rendering its use as natural fertilizer supplement. In this study, the effect of wheat gluten hydrolysate, as biostimulant was studied under in vitro conditions to measure the shoot growth and also the gene expression of enzyme involved in the tricarboxylic acid cycle and nitrogen metabolism. An increased biostimulant activity of the wheat gluten hydrolysate would enable its application in the field of agriculture as a plant based fertilizer that would likely aim at reducing the use of chemical fertilizers and improving crop performance.